Antenatal exposure to nonsteroidal anti‐inflammatory drugs and risk of neonatal hypertension - Habli, Mounira (J Clin Hypertens (Greenwich), 2018)
Nonsteroidal anti‐inflammatory drugs (NSAIDs) are used as tocolytics, which are medications that suppress uterine contractions for preterm birth prevention. Their effect on cerebral/systemic vascular beds poses the question of whether antenatal NSAID exposure is associated with neonatal hypertension. We performed a retrospective case‐control study in a tertiary neonatal intensive care unit, including 40 hypertension cases (hospitalized neonates ≥ 35 weeks with systolic BP > 100 mm Hg on three consecutive days) compared to 134 controls matched by gestational age at delivery, plurality, and delivery date. Cases and controls were compared by antenatal NSAID exposure, other common tocolytics, and maternal/neonatal characteristics and complications. Multivariable logistic regression was used to estimate the odds of hypertension among those with prenatal exposure to NSAIDs versus those without exposure. Newborns with hypertension had a lower gestational age at delivery and increased incidence of neonatal complications, including respiratory distress syndrome, bronchopulmonary dysplasia, surfactant administration, longer duration of ventilation, and history of umbilical artery catheterization. Days of indomethacin exposure were positively associated with greater odds of neonatal hypertension (OR 1.17 [1.00 to 1.38], P = 0.055), even after adjustment for other factors associated with neonatal hypertension. Newborns with hypertension were less likely to have been exposed to calcium channel blockers as a tocolytic. The results of our study suggest an association between prenatal exposure to nonsteroidal anti‐inflammatory drugs and neonatal hypertension. Furthermore, our data suggest that prenatal calcium channel blocker exposure may protect against the development of neonatal hypertension. Future multicenter studies are needed to understand the risks of tocolytics and subsequent consequences in preterm infants.